Jacques Viger: une biographie. Suivi des lettres de Jacques et Marguerite, 1808-1813 - Beaudoin, Léo; Blanchet, Renée (VLB Éditeur, 2009)
Keywords: Lacorne (famille); Maires; Milice; Société historique de Montréal; Viger; Jacques

Récits du XIXe siècle: structure et contenu du discours historiographique au Canada au XIXe siècle: Garneau, Kingsford, Rameau de Saint-Père, Smith - Couture, Claude; Defert, Jean-Jacques (Presses de l'Université Laval, 2009)
Keywords: Histoire; Historiens

L'iconographie rébellienne, la face cachée de l'historiographie des rébellions de 1837-1838: quelques études de cas - St-Jean, France (Mens, 2009)
issued: 2009-23-00
Keywords: Histoire; Rébellions

1858-2008. Numéro souvenir du 150e anniversaire de la Société historique de Montréal (Montréal en tête, 2008)
issued: 2008-23-00
Keywords: Histoire; Historiens; Société historique de Montréal

Les fondateurs de la Société historique de Montréal - Beaudoin, Léo; Bellemare, Georges (Montréal en tête, 2008)
issued: 2008-23-00
Keywords: Baby; Louis-François Georges; Baudry; Joseph-Ubalde; Bellemare; Raphaël; Histoire; Historiens; Huguet-Latour; Louis-Adolphe; Société historique de Montréal; Viger; Jacques

Les lignes de faîte de l'historiographie des rébellions de 1837-1838 - Collin, Marc (Bulletin d'histoire politique, 2008)
issued: 2008-23-00
Keywords: Histoire; Rébellions

The Pictured and the Posed: Nineteenth Century Touristic Images of the Lachine Rapids - Eagan, Mireille M. (Université Concordia, 2008)
Keywords: Lachine; Paysages; Peinture; Photographie; Tourisme

Les archives de la Société historique de Montréal. La contribution de la Société historique de Montréal à la sauvegarde du patrimoine archivistique montréalais - Lebeau, Mireille (Montréal en tête, 2008)
issued: 2008-23-00
Keywords: Archives; Conservation; Histoire; Patrimoine; Société historique de Montréal

"Rien n'est beau que le vrai". L'histoire aux débuts de la Société historique de Montréal - Roy, Fernande (Montréal en tête, 2008)
issued: 2008-23-00
Keywords: Histoire; Historiens; Société historique de Montréal

Louis-François-George Baby (1832-1906). Bourgeois montréalais, cofondateur et 3e président de la Société historique de Montréal - Beaudoin, Léo (Montréal en tête, 2007)
issued: 2007-21-00/2007-22-00
Keywords: Baby; Louis-François Georges; Bourgeoisie; Histoire; Numismatie; Société historique de Montréal

Iberville et les historiens. Le parcours historiographique d'un héros de la Nouvelle-France - Camirand, David (Université de Montréal, 2007)
Keywords: Histoire; Historiens; Le Moyne d'Iberville et d'Ardillières; Pierre

Représentations identitaires - Deslandres, Dominique (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Sulpiciens

L'histoire des Montréalaises: un chantier en construction - Baillargeon, Denyse (Vivre en ville. Bruxelles et Montréal aux XIXe et XXe siècles, 2006)
Keywords: Femmes; Histoire

La route et ses passagers dans les romans rédigés au Québec au XIXe siècle: outils de représentation de la mobilité - Bousquet, Eveline (Université de Montréal, 2006)
Keywords: Roman

The Curious Tale of the Scots and the Fur Trade: An Historiographical Account - Bumsted, J. M. (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Fourrure; Écossais

Autour de Chénier: les Rebellions et la conscience historique canadienne et québécoise - Collin, Marc (Université Laval, 2006)
Keywords: Histoire; Rébellions

David Ross McCord (1844-1930): Imagining a Self, Imagining a Nation - Harvey, Kathryn Nancy (Université McGill, 2006)
This thesis is about the life of David McCord and the contribution he made to Canadian public memory as founder of the McCord Museum of National History. In his McGilI-sponsored museum, founded in 1921, McCord sought to promote a myth of Canadian origins with narration provided by the objects of his personal collection. Integral to this history was the story of the McCord family, their arrival on this continent and their rise to social prominence. In McCord's version of Canadian history, family and personal myth were conflated with that of nation. Viewed through the prism of his collecting and museum work, McCord's life does not easily fit the Carlylean frame adopted by most biographers. In Canadian biographical writing by historians, the 'truth' about a person's life is revealed by following the modernist recipe of painstakingly recreating a detailed chronology of the individual's life. The approach followed here is an important departure from traditional political biography. Entry into McCord's life does not occur at his biological birth date, but at the moment of his own self-fashioned 'birthing', with the opening of the museum realized near the end of his life. In this biographical strategy, McCord's museum acts as a theatre of memory, where fragments of his life story are reassembled to create a narrative of national origins and of personal redemption. In his selection of objects and their display, and in the creation of an archive and the museum itself, McCord left a very elaborate and lasting record of his response to a set of changes associated with industrialization, a process which, in his lifetime, radically transformed the Montreal of his parents' generation. This thesis traces the connection between the creation of a public museum, founded to promote a collective vision of the Canadian past, and the private world of one collector whose collecting practice was defined as much by his own desire to remember and be remembered as it was by the kinds of objects he collected. What makes David McCord's life and collection so compelling is the opportunity it provides from understanding national history from the intimate perspective of one individual.
Keywords: McCord (famille); McCord; David Ross; Musée McCord; Musées

Sir William Logan and Sir J.W. Dawson: Victorian Geology as Scottish Science in a New World Environment - Zeller, Suzanne (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Dawson; William; Géologie; Logan; William Edmond; Écossais

The Stories Told: Indigenous Art Collections, Museums, and National Identities - Dickenson, Rachelle (Université McGill, 2005)
Keywords: Autochtones; Musées

McEACHRAN, DUNCAN McNAB - Goulet, Denis; Jean, Frédéric (Dictionnaire biographique du Canada, 2005)

JETTÉ, JULES - Laugrand, Frédéric (Dictionnaire biographique du Canada, 2005)

Les bouteilles de verre du château de Vaudreuil: une archéologie de l'alcool à Montréal, au XVIIIe siècle - Losier, Catherine (Université de Montréal, 2005)
Keywords: Alcool; Archéologie

McCORD, DAVID ROSS - Miller, Pamela (Dictionnaire biographique du Canada, 2005)

RUTTAN, ROBERT FULFORD - Nicholls, Robert V. V. (Dictionnaire biographique du Canada, 2005)

DUCLOS DE CELLES, ALFRED - Roy, Fernande (Dictionnaire biographique du Canada, 2005)

CAMPBELL, ROBERT - Shute, Dan (Dictionnaire biographique du Canada, 2005)

Seigneur, Faites Que Je Voie: One-man's Quiet(ish) Revolution - Henderson, Robert K. (The Beaver, 2004)
issued: 2004-02/2004-03

Carving the Past in Stone: le Monument aux Patriotes - O'Flaherty, Rosemary (Université Concordia, 2004)
Keywords: Monuments; Rébellions

L'Hôtel Rasco: inventaire et fouille archéologiques au site Le Royer (BjFj-53), 1998: Vieux-Montréal et faubourgs - Arkéos (Ville de Montréal, 2003)
Keywords: Archéologie; Hôtellerie

H.-A. Verreau, ptre (1828-1901). Deuxième président de la Société historique de Montréal (suite*) - Beaudoin, Léo (Montréal en tête, 2003)
issued: 2003-24-00
Keywords: Chauveau; Pierre-Joseph-Olivier; Communautés religieuses; Histoire; Historiens; Société historique de Montréal; École normale Jacques-Cartier; Écoles normales

La contribution entomologique et taxinomique de l'abbé Léon Provancher - Desmeules, Mélanie (Université du Québec à Chicoutimi, 2003)
Keywords: Entomologie; Flore

Duncan McEachran 1841-1924 / Duncan McEachran 1841-1924 - Fulleringer, Pat (Héritage Dorval, 2003)
Number: 1
Keywords: McEachran; Duncan McNab; Université McGill; École de médecine vétérinaire

A Sixty-Year Evolution of Biochemistry at McGill University - Johstone, Rose (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2003)
Keywords: Chimie; Université McGill

Anatomically Incorrect: Bodysnatching in the Nineteenth Century - Rankin, Matthew (The Beaver, 2002)
issued: 2002-08/2002-11
Keywords: Criminalité; Médecine; Université McGill; Étudiants

H.-A. Verreau, ptre (1828-1901). Deuxième président de la Société historique de Montréal - Beaudoin, Léo (Montréal en tête, 2002)
issued: 2002-23-00
Keywords: Chauveau; Pierre-Joseph-Olivier; Communautés religieuses; Histoire; Historiens; Société historique de Montréal; École normale Jacques-Cartier; Écoles normales

Toronto vs Montreal: The Struggle for Financial Hegemony, 1860-1875 - Masters, D.C. (The Contested Past: Reading Canada's History - Selections from the Canadian Historical Review, 2002)
Keywords: Banques; Métropole

Les Canadiens français, l'histoire et la démocratie: l'interprétation de Pierre Elliott Trudeau - Ouellette, Mélanie (Mens, 2000)
issued: 2000-23-00
Keywords: Trudeau; Pierre Elliott

La recherche sur l'histoire de la presse québécoise. Bilan et perspectives - Roy, Fernande (Recherches sociographiques, 2000)
Number: 1
Keywords: Histoire